Trust and Confidence in Media and Criminal Justice Institutions - Boateng, Francis D. (International journal of offender therapy and comparative criminology, 2019)
In every society, the main purpose of the criminal justice system is to maintain social order and ensure that citizens comply with the law. To do this effectively, the police and court systems need citizen cooperation and obedience, and willingness to assist with criminal investigations and report crimes to the police. The purpose of this study is to examine the association between confidence in the media and confidence in the criminal justice institutions in South Africa. The study tests two objectives: to assess South Africans' level of confidence in the police and courts, and to determine whether citizens' levels of confidence in both the print and televised media will influence their levels of confidence in the police, courts, and in the criminal justice system in general. Utilizing data from the World Values Survey, results reveal a significant and positive relationship between confidence in the media and confidence in the criminal justice institutions. Policy implications of this observation are discussed.